2013
DOI: 10.1007/s40263-013-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Understanding the Pathophysiology of Post-Traumatic Stress Disorder

Abstract: Post-traumatic stress disorder (PTSD) is a common and chronic anxiety disorder that can result after exposure to a traumatic event. Though our understanding of the aetiology of PTSD is incomplete, several neurobiological systems have been implicated in the pathophysiology and vulnerability towards developing PTSD after trauma exposure. We aimed to provide a concise review of benchmark findings in important neurobiological systems related to the aetiology and maintenance of PTSD symptomology. Specifically, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 185 publications
(198 reference statements)
2
64
0
2
Order By: Relevance
“…Alternatively, the effects of a hypernoradrenergic state in the amygdala could be mediated by β1-adrenoreceptors since propranolol is a nonselective beta blocker. Also, an increased activity of other neurotransmitter systems in the amygdala such as the serotoninergic projections from the raphe (Bailey et al, 2013;Hendriksen et al, 2014;Pitman et al, 2012) might be necessary for the expression of hyperarousal symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the effects of a hypernoradrenergic state in the amygdala could be mediated by β1-adrenoreceptors since propranolol is a nonselective beta blocker. Also, an increased activity of other neurotransmitter systems in the amygdala such as the serotoninergic projections from the raphe (Bailey et al, 2013;Hendriksen et al, 2014;Pitman et al, 2012) might be necessary for the expression of hyperarousal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we evaluated the mRNA levels of β1-and β2-adrenergic receptors in the amygdala. Previous studies have shown that the alteration in the activity of the circuit prefrontal cortexhippocampus-amygdala is involved in the pathophysiology of PTSD (Bailey et al, 2013;Hendriksen et al, 2014;Pitman et al, 2012). Thus, we evaluated the expression of the β-adrenergic receptors in these three areas of the brain (see table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The type and duration of trauma, psychological factors like personality characteristics, gender, and biological factors all seem to play a significant role in PTSD aetiology (Yehuda et al 1995, Breslau et al 1997, Frans et al 2005). Several mechanisms have been implicated in the pathophysiology of PTSD including genetics, epigenetics, and neurobiological systems (Pitman et al 2012, Bailey et al 2013, Ryan et al 2016. Recently, PTSD research has focused on immune mechanisms, for example, peripheral blood mononuclear cells (PBMCs) and cytokines, such as tumor necrosis factor-alpha (TNF-; Andrews & Neises 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One such region that contains a large percentage of chemosensitive neurons is the locus coeruleus (LC). The LC is an important noradrenergic region in the pons and has been implicated to play a role in many pathological conditions, including panic disorder, Rett syndrome, and posttraumatic stress disorder (1,55,65,66). In addition, chemosensitive LC neurons are believed to be a part of a distributed network of neurons that are involved in the control of breathing (18,35).…”
mentioning
confidence: 99%